Dinamika Faktor-Faktor Resiliensi pada Remaja yang Pernah Mengalami Kerusuhan di Ambon Tahun 1998 - Yunus, Affidina Chantal; Putra, Denny (Noetic Psychology, 2012)
AbstractAmbon riot in 1999 has caused damage to children and teenager victim. This children and teenager need resilient to help them survive and dealing with their traumatic experience. Based on this, the researcher want to explore the resilient factorÃÂ among teenager who experience the Ambon riot. Qualitative methods was used in this research. The subject of this research was two 15-18 years old teenager who lived in Yayasan Bersinar Orphant care, Jakarta. The research found thatÃÂ there were differences in the resilient factor (I Have, I am and I can) among two subject. There were also found a significant changes in the subject live between when they were in Ambon and after they were in Jakarta. The conclusion of this research was the resilient factor played an important factor in oneÃ¢â¬â¢s life.ÃÂ Keywords : resiliency, resilient factors, Ambon riotÃÂ